The Role Of The Development Of Small Business And Private Entrepreneurship In The Provision Of Employment: A Case Study Of The Republic Of Uzbekistan - Ziyadullayevich, Ibrgagimov Lutfullo (European Scientific Journal, ESJ, 2016)
This study focuses on the development of small business and private entrepreneurship in the provision of employment for the teaming population of the Republic of Uzbekistan. It is one of the main indicators used in identifying not only the economic situation of the people, but also the lifestyle of the people, especially where they live. One of the main issues affecting the program of employment of the population and in organizing new replacements in Uzbekistan is in paying attention as global tasks of small business and enterprise. However, this aims to increase the role of farm activity, sevice, social and market infrastructure, and the development of other beneficiary types of employment. In this article, the main characteristics of the development of small business were stated. In addition, one of the major problems of the employment of the population was also outlined.